The Effect of Rewards and Green Human Resource Management on Employee Turnover at the Sukoharjo District Land Office - Mohamad Izza Fathan; Imronudin Imronudin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study explores the influence of rewards and Green Human Resource Management (GHRM) practices on employee turnover at the Sukoharjo District Land Office, with job satisfaction as a mediating variable. Using Social Exchange Theory and Herzberg’s Two-Factor Theory as the theoretical foundation, the research employed a quantitative method with PLS-SEM to analyze data from 85 purposively selected employees. Rewards included both financial (e.g., bonuses) and non-financial (e.g., recognition), while GHRM encompassed eco-friendly recruitment, environmental training, and employee engagement in sustainability programs. Results show that both rewards and GHRM significantly reduce turnover, with job satisfaction partially mediating these effects, enhancing the impact when employees feel valued and motivated. Among GHRM components, environmental training and participatory green initiatives proved most effective. Despite its contributions, the study is limited to a single public institution and does not address other potential turnover factors such as leadership, work-life balance, or career development. Future research should broaden the context and apply mixed methods to deepen understanding of sustainable HRM strategies.